The relationship between knowledge sourcing and fear of imitation - Giarratana, Marco S.; Mariani, Myriam (Strategic Management Journal, 2014)
When firms tap external knowledge sources, they risk spillovers of their own internal knowledge. If the value of this potential loss and the imitation capabilities of neighboring organizations are high, fear of imitation might overshadow the benefits of openness. In such situations, firms might voluntarily reduce their use of external sources, relative to knowledge available internally. Data pertaining to 4,623 European inventions and direct information about the use of knowledge sources confirm that firms reduce their use of external, relative to internal, knowledge when they conduct costly research projects in locations characterized by high levels of absorptive capacity in a specific technology. This study also reveals fear of imitation as a mediating factor of this behavior . Copyright © 2013 John Wiley & Sons, Ltd.